Husband's rights between duty and responsibility: A legal and Islamic Sharia Analysis - Rania, Benahmed; Mokhtar, Baroudi (The International tax journal, 2025)
Marriage has existed since ancient times, yet it was not organized in the structured manner we see today until the intervention of Islamic law. Islamic law provided comprehensive teachings that guided the formation of marriage and continued to oversee it until its termination, either through the death of one of the parties or their separation for any reason. Islamic law elucidates the conditions and essential elements required for a valid marriage, as well as its effects on the spouses and others. It specifies the rights and obligations of both parties, aiming to prevent confusion and abuse within the marital relationship.